Simultaneous design of the optimal reaction and process concept for multiphase systems - Hentschel, Benjamin; Peschel, Andreas; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Science, 2014)
In complex chemical processes optimizing the reactor with respect to a stand-alone reactor performance criterium such as product selectivity does not necessarily yield the best process-wide reaction concept. Especially in case of multiphase reaction systems, which often involve complex reaction networks, nonideal phase behavior and multiple recycles, reactor and process have to be optimized simultaneously since the reactor affects the separation units and vice versa. In order to derive the process-wide optimal reaction concept in combination with optimal process parameters, a systematic optimization procedure based on a large scale optimization problem constrained by a system of differential algebraic equations (DAE) is presented. The optimization problem contains a detailed model of the reaction section, a process model describing the other units of the process, and models for operational and fixed costs. The solution of the optimization is a set of process parameters and optimal profiles of heat and material fluxes over the reaction coordinate which minimize the production costs. The method is exemplified on the rhodium catalyzed hydroformylation of 1-dodecene in a thermomorphic solvent system. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reactor design; Process design; Simultaneous optimization; Multiphase systems; Hydroformylation; Process economics